2022
DOI: 10.3389/fbioe.2022.1000401
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the superhydrophilicity-modified titanium surfaces with antibacterial and pro-osteogenesis properties: A review

Abstract: In recent years, the rate of implant failure has been increasing. Microbial infection was the primary cause, and the main stages included bacterial adhesion, biofilm formation, and severe inhibition of implant osseointegration. Various biomaterials and their preparation methods have emerged to produce specific implants with antimicrobial or bactericidal properties to reduce implant infection caused by bacterial adhesion and effectively promote bone and implant integration. In this study, we reviewed the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…Rapid adsorption of biological molecules is initiated at the beginning, soon after the implantation by the implant surface wetting property . The superhydrophilic nature of the implant surfaces is today’s trend in implantology Figure b shows the graph with the wettability profile of samples from water contact angle (WCA) measurements.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Rapid adsorption of biological molecules is initiated at the beginning, soon after the implantation by the implant surface wetting property . The superhydrophilic nature of the implant surfaces is today’s trend in implantology Figure b shows the graph with the wettability profile of samples from water contact angle (WCA) measurements.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The plasma-treated Ti surface has a reduction potential, leading to oxidation of the surrounding environment. In addition, TiO 2 could be modified by ions, such as COOH − , OH − , NO − , N 3− and O 2after plasma treatment (Lee et al, 2019;Shao et al, 2022).…”
Section: Plasma Treatment Surfacementioning
confidence: 99%
“…Reactive oxygen and nitrogen species are the main active components of non-thermal plasma, enabling titanium surface perform reductive potential which oxidize the surrounding material ( Lee et al, 2019 ; Shao et al, 2022 ). Monetta and Bellucci (2014) proposed that oxygen cold plasma treatment can increase the content of TiO 2 on the surface of titanium samples and promote the anatase formation.…”
Section: Titanium Alloys With Antibacterial Properties In a Reactive ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study obtained superhydrophilic implant surface by atmospheric-pressure plasma treatment, and confirmed that the superhydrophilic implant can induce high hard-tissue differentiation in vivo [ 26 ]. In addition to promoting bone formation, superhydrophilic surfaces can inhibit bacterial adhesion and viability [ 27 ].…”
Section: Introductionmentioning
confidence: 99%